28 Diagnosed vs Undiagnosed Chronic Obstructive Pulmonary Disease: Short and Long-term Impact on Coronary Artery Bypass Surgery. (4th May 2021) - Gatta, F; Haqzad, Y; Loubani, M
Abstract: Introduction: This study sought to compare clinical outcomes among non-COPD, diagnosed COPD, and undiagnosed COPD patients, in CABG surgery. Method: A single-centred retrospective study, from January 2010 to December 2019. Primary outcomes were post-operative complications, lenght of ITU admission and in-hospital staying. Secondary outcomes were re-intervention rate, in-hospital and long-term mortality. Results: 4020 patients were divided into: non-COPD – Group A (74.55% n = 2997), diagnosed COPD – Group B (14.78% n = 594), and undiagnosed COPD – Group C (10.67% n = 429). The rate of respiratory complications was noted in this order: Group B > Group C > Group A (p 0.00000002). Perioperative Acute Kidney Injury, wound complications, and in-hospital staying were higher in Group B (p 0.0004, p 0.03, and p 0.0009, respectively). Long-term mortality resulted greater in Group B and C (p 0.0004). No difference in long-term mortality was noted in relation to the expected FEV1% in Group B (p 0.29) and Group C (p 0.82). Conclusions: In CABG surgery, patients with diagnosed COPD carry a prolonged in-hospital staying and greater peri-operative complications. Both diagnosed and undiagnosed COPD predispose to respiratory complications and higher long-term mortality rate. Consequently, undiagnosed COPD should be included in the EuroSCORE. Finally, the expected FEV1% appears not to correlate with long-term survival.